1992
DOI: 10.1093/oxfordjournals.annonc.a058185
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon alfa-2a with or without vinblastine in metastatic renal cell carcinoma: Results of a European multi-center phase III study

Abstract: A total of 178 patients with metastatic renal cell cancer were randomized to receive interferon alfa-2a (rIFN alfa-2a) or interferon alfa-2a+vinblastine (VLB). IFN alfa-2a was injected intramuscularly at a dose of 18 MIU 3 times a week and VLB was given intravenously at a dose of 0.1 mg/kg once every 3 weeks. The response rate was 11% for patients on monotherapy and 24% for those on combination treatment. The 5-year survival for 145 eligible patients was 9%, independently from the treatment arm. The performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(38 citation statements)
references
References 21 publications
0
37
0
1
Order By: Relevance
“…Although immunotherapy has been successfully used for treating tumors in animal model, only few types of tumors such as melanoma and renal cell carcinoma responded to immunotherapy using IL-2 and IFN-a [4][5][6]. Systemic administration of cytokines often causes severe adverse effect at higher doses that can induce efficient antitumor effects in several human tumors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although immunotherapy has been successfully used for treating tumors in animal model, only few types of tumors such as melanoma and renal cell carcinoma responded to immunotherapy using IL-2 and IFN-a [4][5][6]. Systemic administration of cytokines often causes severe adverse effect at higher doses that can induce efficient antitumor effects in several human tumors [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Median survival was also significantly different between the 2 groups (15.8 mo v. 8.8 mo). Fossa and others 13 randomized 178 patients to receive interferon-α2a or interferon-α2a with vinblastine with the exact same dosages as those used in the study by Pyrhonen and others. 12 Like that study, Fossa and others 13 found vinblastine increased RR (from 11% to 24%), but unlike that study, they found no difference in survival rate between the 2 groups.…”
Section: Interferonsmentioning
confidence: 99%
“…Fossa and others 13 randomized 178 patients to receive interferon-α2a or interferon-α2a with vinblastine with the exact same dosages as those used in the study by Pyrhonen and others. 12 Like that study, Fossa and others 13 found vinblastine increased RR (from 11% to 24%), but unlike that study, they found no difference in survival rate between the 2 groups. Differences in the calculation of survival may explain the difference in conclusions: Pyrhonen and others 12 calculated survival in months, whereas Fossa and others 13 compared the percentage of surviving patients.…”
Section: Interferonsmentioning
confidence: 99%
“…In this context it is also of interest to emphasize that controlled randomized trials evaluating different approaches of immunotherapy on survival, for example IL-2 vs IL-2 plus lymphokine-activated killer cells or IFN-a vs IFN-a and vinblastin, displayed no significant differences (Fossa et al, 1992;Rosenberg et al, 1993;Kellokumpu-Lehtinen et al, 1995). Furthermore, the advantage of an increased response rate after immunological manipulation has not always been translated to a better chance of survival (Fossaet al, 1992;Facendola et al, 1995).…”
Section: Final Analysismentioning
confidence: 99%